(untitled) (Libya Journal of Geographical Studies, 2025)
The study shows the analysis of spatial differences in agricultural land uses, and this is confirmed by the results of spatial statistical analysis between the selected agricultural districts, which were classified based on the creation of statistical spatial maps with real results using spatial statistical Analysis applications (Spatial statistical Analysis) and the cluster analysis method using Moran’s Moran’s (I) Method in modeling the spatial distribution of agricultural land uses in tuzkhurmatu district. Spatial statistical processing and analysis in geographic information systems (GIS) is an effective tool to identify spatial differences, relationships and correlations between different geographical phenomena, which makes it possible to accurately assess the use of agricultural land, determine the suitability of the land for agriculture and the potential for its development, as the research found that the distribution of wheat growing areas in the region shows a semi-random pattern, where the Moran index reached 0.193, Z-Score Value 1.32, and P-Value 0.186, which indicates the absence of a clear spatial grouping of the distribution of land planted with wheat, meaning this is the absence of a specific geographical organization at the significance levels of 0.05 and 0.10.